Annulment of the marriage contract due to marital defects ( A comparative study ) - Salman Rajab, Researcher. Hussam El-Din; Abdul Ali Al-Asadi, Prof.Dr. Ali; Abdel Samad Al Shawi, Prof. Dr. Abdel Basset (Basra studies journal, 2025)
The marriage contract is an important and dangerous contract because it constitutes the first nucleus of society, and the stability of marital life leads to a society free of gaps that threaten its stability. The contract must be built on strong foundations free of deprivations and defects that may invalidate it or deprive it of its essence. Islam is keen on the permanence of the marriage contract and allows divorce in cases where continuing the contract is difficult or impossible. The dissolution of the marriage contract varies, such as divorce, judicial separation, divorce, and annulment. The contract is dissolved for various reasons, such as the impossibility of its continuation, change of religion, or the presence of marital defects that negatively affect the other partner. The study focuses on the impact of these defects on the marriage contract and its continuity, and identifies the defects that jurists consider to be a reason for annulment based on differences in viewpoints and personal status laws in some Arab countries. The study is divided into two sections, where the first section focuses on defining the annulment of the marriage contract and analyzing the defects specific to men and women, as well as the defects that affect both spouses, while presenting the opinions of jurists on the possibility of annulment of the contract because of them. In the second section, the focus is on the position of personal status laws, and an analysis of the personal status laws in Iraq, Yemen, Kuwait, and Jordan, to compare them and understand how to deal with cases of annulment of the marriage contract.